2008 IEEE Sensors 2008
DOI: 10.1109/icsens.2008.4716406
|View full text |Cite
|
Sign up to set email alerts
|

Performance and reliability of MEMS coatings in liquids

Abstract: Reliability of MEMS in liquids is an importantconcern for MEMS operating in harsh environments in petrochemical, biomedical, and defense applications. Our previous studies have demonstrated reliability concerns for silicon microcantilevers in liquid environments such as saline. In this paper, the effect of coatings on reliability of MEMS in liquids, such as DI water and saline, is compared to that in air. Silicon microcantilevers coated with Titanium (Ti) and SU-8 were vibrated in liquids for 10 8 -10 9 cycles… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2011
2011
2014
2014

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 9 publications
1
0
0
Order By: Relevance
“…18) However, Ali et al reported that absorption of water in the material can lead to swelling and to a residual strain in SU-8 cantilevers. 19) This phenomenon was also observed by Feng et al who assumed a reversible mechanism. 20) These authors concluded that the resulting strain can be minimized by applying a drying process.…”
Section: Introductionsupporting
confidence: 62%
“…18) However, Ali et al reported that absorption of water in the material can lead to swelling and to a residual strain in SU-8 cantilevers. 19) This phenomenon was also observed by Feng et al who assumed a reversible mechanism. 20) These authors concluded that the resulting strain can be minimized by applying a drying process.…”
Section: Introductionsupporting
confidence: 62%